How Intern Doctors View ‘Psychiatry and Mental health’? - Shakya, D.R. (Journal of Psychiatrists' Association of Nepal, 2018)
Introduction: The knowledge and attitude prevailing during internship of medical education are likely to influence whole career. Psychiatry is seen differently, at times unrealistically. Such views might have adverse consequences. The objective of this study was to assess knowledge and views of intern MBBS doctors of B. P. Koirala Institute of Health Sciences, Nepal about ‘Psychiatry and mental health’.Material and Method: A cross-sectional semi-qualitative survey was done by explaining about the study, distributing a questionnaire and analysing collected samples of the interns.Results: Within study period, 50 respondents participated. Twenty percent respondents were female. One-third subjects were from Kathmandu valley, followed by other cities of Nepal and India. Two-thirds opted psychiatry posting, half to learn about it. About 25% considered psychiatry for career. Majority viewed psychiatry should integrate with other departments. Only few meant mental illness to be unremitting and chronic only, and considered mental patients dangerous and aggressive. More believed that majority of patients understand others’ feelings, attitudes and behavior; and can be productive if treated appropriately. A great majority felt that the management should be multi-sectorial and multi-dimensional. They expressed dissatisfaction about current position of mental health on national health-policy and advised public awareness as the most important step to change the situation.Conclusion: Intern-doctors of a tertiary-care teaching hospital with psychiatry teaching, in overall, have favorable attitude towards psychiatry and mental health.